2017
DOI: 10.3390/ijerph14060637
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium Intake and Adherence to the Mediterranean Diet in Spanish Children: The ANIVA Study

Abstract: The aim of this study was to evaluate the relationship of dietary calcium intake with anthropometric measures, physical activity and adherence to the Mediterranean diet (MedDiet) in 1176 Spanish children aged 6–9 years. Data were obtained from “Antropometría y Nutrición Infantil de Valencia” (ANIVA), a cross-sectional study of a representative sample. Dietary calcium intake assessed from three-day food records was compared to recommended daily intakes in Spain. Anthropometric measures (weight and height) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Yogurt represents an important food item in children's diet because many families consider it a main source of Ca in their diet. However, a recent study with Spanish schoolchildren found that the consumption of dairy products was insufficient to impact total Ca intake (36) . To further investigate the role of yogurts in children's diet, we presented two scenarios: (1) yogurts were classified as unprocessed food or MPF (unsweetened) or (2) yogurts were classified as UPF (sweetened).…”
Section: Discussionmentioning
confidence: 99%
“…Yogurt represents an important food item in children's diet because many families consider it a main source of Ca in their diet. However, a recent study with Spanish schoolchildren found that the consumption of dairy products was insufficient to impact total Ca intake (36) . To further investigate the role of yogurts in children's diet, we presented two scenarios: (1) yogurts were classified as unprocessed food or MPF (unsweetened) or (2) yogurts were classified as UPF (sweetened).…”
Section: Discussionmentioning
confidence: 99%
“…Since children with a medium/high adherence to the MD have a more balanced diet in terms of nutrients and functional foods [ 10 ], these habits can explain our data. In particular, a diet poor in micronutrients and high-quality proteins from milk products, pork meat, and fish has been shown to negatively influence stature [ 42 , 43 , 44 ]. The reanalysis of data derived by HELENA and IDEFICS cohorts could confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For our data, the single and married cate- This common purchasing behavior can be better understood through ethnographic data related to food nutrition. From an anthropological point of view, dairy products are considered healthy foods globally, being recommended especially for dietary calcium intake [70]. Ethnographically, however, there are some specific differences.…”
Section: Sustainability 2021 13 X For Peer Review 13 Of 23mentioning
confidence: 99%